Some aspects of the nitrogen nutrition and growth of Gracilaria gracilis grown by suspended cultivation in Saldanha Bay, South Africa - Wilson, Daniel T (Department of Biological Sciences, 2017)
For suspended cultivation of seaweeds in the open ocean, the selection of suitable sites and the optimization of cultivation methods for maximum productivity are of utmost importance. Growth of raft-cultivated Gracilaria gracilis in Saldanha Bay is known to be badly affected in late summer due to the persistence of warm oligotrophic water at the ocean surface which prevents replenishment of nutrients by upwelling. This study documents the extent of nitrogen starvation during this period and investigates some possible methods of managing this problem. Nitrogen content, C:N ratio and stable isotope abundances of C and N were obtained for material grown for varying lengths of time, material grown at various depths and material that had been fertilized prior to placement on the raft. The relationship between thallus colour and nitrogen content was also documented using a standard colour guide. The onset of nitrogen starvation was rapid, occurring after about two weeks on the raft. Growth was optimized about a meter below the water surface, possibly as a result of photoinhibition of photosynthesis at the surface. Nitrogen limitation ceased below about 2m growth depth. Prefertilization had no significant effect on yield after 4 weeks growth. Thallus colour showed a clear relationship with N content and may be a useful indicator of N status of cultivated Gracilaria. δ¹⁵N was related to N content and increased rapidly when N limitation was removed. Stable isotope natural abundance measurements are a useful tool in the study of growth environment, but more controlled experimentation investigating the factors which influence these values is needed, particularly for macroalgae.